Quartz backed tools as arrowheads and hand-cast spearheads: Hunting experiments and macro-fracture analysis. (September 2016) - Pargeter, Justin; Shea, John; Utting, Benjamin
Abstract: The invention of the bow and arrow was a milestone in Late Pleistocene technological evolution. Preservation biases and methodological problems imped our ability to detect its presence in the archaeological record. Currently, South Africa has the earliest suggested evidence for arrowheads, amongst others, small quartz backed tools dating 65–60 ka. These artefacts' inferred function is based on their small size, micro and macro wear traces and micro-residues recorded on quartz segments from Sibudu Cave. Experimental support for these inferences, or to show that similar artefacts are associated with bow hunting, are however lacking. Here we describe breakage patterns on 150 quartz backed tools hafted as transverse arrowheads and hand-cast spearheads in simulated hunting experiments. These experiments controlled for hafting variability to test the effects of propulsion velocity on the types, patterns and area of diagnostic impact fractures (DIFs). Our results show step terminating bending fracture, spin-off fracture and impactburination frequencies, DIF locations, and ventrally situated DIF frequencies to be robust means of distinguishing arrowheads from spearheads. Our experiments verify previous observations that overall DIF frequencies differentiate between these weapon types. Importantly, we confirm that DIF size is linked to weapon propulsion velocity, but that fracture area is affected by tool area. These findings provide methods for future testing of the hypothesis that bow and arrow technology was in use at least 65 ka in southern Africa and in other regions where quartz was used to tip weapons. Highlights: We distinguish quartz segments as transverse arrowheads and hand-cast spearheads. DIF frequencies differentiate between these two weapon types. DIF area, adjusted by tool area, is indicative of weapon type. These results have wide applicability for quartz assemblages.